Characteristics of babies who unexpectedly survive long term after withdrawal of intensive care. (23rd December 2015) - Pal, Sanchita; Jones, Jacqueline; Job, Sajeev; Maynard, Linda; Curley, Anna; Clarke, Paul
Abstract: Aim: Occasional babies survive long term after withdrawal of intensive care despite a poor prognosis. We aimed to review in detail the clinical cases, characteristics, and outcomes of neonates with unexpected protracted survival following planned withdrawal of intensive cardiorespiratory support. Methods: We reviewed infants who unexpectedly survived for more than one week following planned withdrawal of intensive care in two tertiary‐level NICUs over a seven‐year period. Results: We identified eight long‐term survivors (six term, two preterm) between 2007 and 2013. All had a clinical diagnosis of grade 3 hypoxic‐ischaemic encephalopathy and severely abnormal electroencephalography and neuroimaging prior to intensive care withdrawal. Intensive care was withdrawn at five days postnatal age (range: two to nine days), but the possibility of protracted survival was discussed beforehand in only two cases. Three infants died before three months of age. Five infants remain alive, currently aged from 2.0 to 6.5 years, and all have significant neurodevelopmental problems. Conclusion: Unexpected long‐term survival after neonatal intensive care withdrawal occurs occasionally but unpredictably. Significant neurodevelopmental adversity was invariable in those surviving beyond infancy. Ventilator dependency along with severely abnormal electroencephalography and neuroimaging is still compatible with long‐term survival. The possibility of protracted survival should be discussed routinely with parents before intensive care withdrawal. Abstract :